Effects of Fungicides on Mold Resistance and Mechanical Properties of Wood and Bamboo Flour/High-Density Polyethylene Composites - Jing Feng; Huiping Zhang; Hui He; Xiaomo Huang; Qingshan Shi (BioResources, 2016)
The main objective of this study was to determine the mold resistance and mechanical properties of fungicide-treated wood and bamboo flour/high density polyethylene (HDPE) composites. Zinc borate (ZB), 4,5-dichloro-2-octyl-isothiazolone (DCOIT), zinc pyrithione (ZPT), and carbendazim (MBC) were used as fungicides. Then, treated and untreated samples were exposed to mold fungi (Aspergillus niger, Trichoderma viride, Penicillium funiculosum, and Aureobasidium pullulans) for 28 days. Mechanical properties, including the tensile strength, modulus of elasticity (MOE), modulus of rupture (MOR), and impact strength of treated and untreated composites, were evaluated. The experimental results indicated that incorporation of all four fungicides greatly improved the mold resistance of wood flour/HDPE composites. ZB-, DCOIT-, and ZPT-treated bamboo flour/HDPE composites were also more resistant to mold fungi, while no inhibitory effect on mold growth was observed for MBC-treated bamboo flour/HDPE composites. In most cases, fungicides lowered the tensile strengths and MOR of wood flour/HDPE samples but increased the impact strengths of wood flour/HDPE composites and tensile strengths and MOE of bamboo flour/HDPE composites, while other mechanical properties behaved differently. Accordingly, some fungicides can be effectively used as preservatives for both wood flour/HDPE and bamboo flour/HDPE composites.